Relevansi Nilai–Nilai Pancasila Dalam Menghadapi Kasus Pelanggaran Hak Asasi Manusia di Indonesia - Jibran, Reynaldi Idil; Putri J, Ainun Amalia; Aulia, Rani; Nadya, Rina (Media Hukum Indonesia (MHI), 2024)
Pancasila also emphasizes the importance of maintaining the unity and integrity of the Indonesian nation and respecting social differences and diversity. Therefore, human rights are not only just individual rights, but also the basis of national and state life peacefully, justly and prosperously. The Indonesian government has made various efforts to protect and promote human rights through the establishment of institutions such as the Commission National Human Rights Commission (Komnas HAM) which has a mission to monitor and protect human rights in Indonesia. Apart from that, Indonesia has also ratified it various international instruments related to human rights, such as the Universal Declaration of Rights Human Rights and the International Convention on Civil and Political Rights. But protection of rights Human rights in Indonesia still face challenges, especially related to incidents of human rights violations that continue to occur in various regions. Therefore, it is important for all actors, both government and society, to remain committed to upholding and protecting human rights as part of efforts to build a just, democratic and civilized society.Pancasila also emphasizes the importance of maintaining the unity and integrity of the Indonesian nation and respecting social differences and diversity. Therefore, human rights are not only just individual rights, but also the basis of national and state life peacefully, justly and prosperously. The Indonesian government has made various efforts to protect and promote human rights through the establishment of institutions such as the Commission National Human Rights Commission (Komnas HAM) which has a mission to monitor and protect human rights in Indonesia. Apart from that, Indonesia has also ratified it various international instruments related to human rights, such as the Universal Declaration of Rights Human Rights and the International Convention on Civil and Political Rights. But protection of rights Human rights in Indonesia still face challenges, especially related to incidents of human rights violations that continue to occur in various regions. Therefore, it is important for all actors, both government and society, to remain committed to upholding and protecting human rights as part of efforts to build a just, democratic and civilized society.